Epithelial–Mesenchymal Transition Participates in the Formation of Vestibular Flat Epithelium - He, Lu; Wang, Guo-Peng; Guo, Jing-Ying; Chen, Zhong-Rui; Liu, Ke; Gong, Shu-Sheng (Frontiers in Molecular Neuroscience, 2021)
The vestibular sensory epithelium of humans and mice may degenerate into a layer of flat cells, known as flat epithelium (FE), after a severe lesion. However, the pathogenesis of vestibular FE remains unclear. To determine whether the epithelial–mesenchymal transition (EMT) participates in the formation of vestibular FE, we used a well-established mouse model in which FE was induced in the utricle by an injection of streptomycin into the inner ear. The mesenchymal and epithelial cell markers and cell proliferation were examined using immunofluorescence staining and quantitative reverse transcription polymerase chain reaction (qRT-PCR). The function of the EMT was assessed through transcriptome microarray analysis. The results demonstrated that mesenchymal cell markers (α-SMA, S100A4, vimentin, and Fn1) were upregulated in vestibular FE compared with the normal utricle. Robust cell proliferation, which was absent in the normal status, was observed in the formation of FE. Microarray analysis identified 1,227 upregulated and 962 downregulated genes in vestibular FE. Gene ontology (GO) analysis revealed that differentially expressed genes were highly associated with several EMT-related GO terms, such as cell adhesion, cell migration, and extracellular matrix. Pathway interaction network analysis showed that EMT-related signaling pathways, such as MAPK and PI3K/Akt, were in the center of the cluster. Protein–protein interaction networks screened 20 hub genes including Nras, Hgf, Thbs1, Col1a1, Il1b, Jun, Myc, Tgfb1, Casp3, Akt1, Irs1, Igf1, Fn1, Itga5, Mapk1, Col1a2, Col2a1, Pdgfrb, Trp53, and Itga2. Most of these genes are reportedly involved in the EMT process in various tissues. The mRNA expression level of hub genes was validated using qRT-PCR. In conclusion, the present study indicates that EMT plays a significant role in the formation of vestibular FE and provides an overview of transcriptome characteristics in vestibular FE.